1999
DOI: 10.1007/s002770050475
|View full text |Cite
|
Sign up to set email alerts
|

Suppressed neutrophil function as a risk factor for severe infection after cytotoxic chemotherapy in patients with acute nonlymphocytic leukemia

Abstract: Severe infections are a major problem in patients suffering from acute nonlymphocytic leukemia (ANLL) undergoing myeloablative chemotherapy. Possible factors leading to infectious complications in these patients are suppressed immune defense mechanisms existing prior to therapy, including those involving the neutrophil granulocyte department. In this study we investigated whether neutrophil function as measured by oxidative burst and phagocytosis before the start of treatment correlates with the severity of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
5

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 8 publications
1
18
0
5
Order By: Relevance
“…Secondly, the functional capabilities of phagocytes such as neutrophils, eosinophils and mononuclear cells may be intrinsically defective even before the initiation of chemotherapy. A study performed by HÜ BEL et al [11] showed cancer patients having preactivated phagocytes with suppressed function prior to initiation of treatment. Thirdly, humoral and cellular immune mechanisms mediated by B and T lymphocytes, respectively, can be profoundly altered in patients with solid cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the functional capabilities of phagocytes such as neutrophils, eosinophils and mononuclear cells may be intrinsically defective even before the initiation of chemotherapy. A study performed by HÜ BEL et al [11] showed cancer patients having preactivated phagocytes with suppressed function prior to initiation of treatment. Thirdly, humoral and cellular immune mechanisms mediated by B and T lymphocytes, respectively, can be profoundly altered in patients with solid cancer.…”
Section: Discussionmentioning
confidence: 99%
“…3 Suppressed neutrophil function, which has been found in patients with acute non-lymphocytic leukaemia, is believed to be related to infection after cytotoxic chemotherapy. 4,5 However, Ziegler et al 6 reported a lower incidence of infection complications in bone marrow transplant recipients receiving supplemental glutamine.…”
Section: Abstract: Glutamine Dipeptide; Acute Myeloid Leukaemia; Neumentioning
confidence: 99%
“…Finally, we propose that by repeating the above-described 5-step protocol at several time points after chemotherapy (see ref. 30), separately fitting at step (e) the parameters at each time point, one may examine whether a significant change in neutrophil function has occurred.…”
Section: Figurementioning
confidence: 99%